Effect of Moringa oleifera (Lam) Leaf Extract on Mating Readiness and Development of Rabbit Ovarian Follicles - setiasih setiasih (Gontor AGROTECH Science Journal, 2020)
Moringa oleifera (Lam) is feed rich nutrients and bioactive compaunds including phytosterogen types namely phytosterols and isoflavones.  The purpose of thid study was to test moringa leaf extracts with diferent solvents against mating readiness and ovarian foliccle development in rabbit does. Three moringa leaf extracts namely ethanol coarse extract (EKE) ethanol fraction extract (EFE) and hexan fraction extract (EFH) were used in this study. Seven treatments were tried on 28 rabbit does in the extracts in pellet feed at a dose of 0 % (without extract), EFH 0.13%, EFH 0.26%, EFE 0.37, EFE 0.74%, EKE 0.54% and EKE 1.08%.  Each treatment is repeated on 4 tails rabbit does. The variables in this study were mating readiness and histology of ovarian follicle development. The results showed that the treatment of EFH administration of 0.26% caused 100% mating readiness and 75% pregnancy rate.  The addition of EFH, EFE and EKE treatment led to a decrease in follicle development in the ovaries of lactation rabbit mothers on day 28. From this study it was concluded that the administration of moringa leaf extract increases blood estradiol, resulting in passionate livestock but has the effect of lowering follicle development in the ovaries of rabbits.